Analysis of Influencer Strategies in Shaping Young People’s Wellness Lifestyles in Bali - Ayu Made Bianca Juarez; Sahri Aflah Ramadiansyah; Putri Ekaresty Haes (Pasundan Social Science Development, 2026)
The proliferation of digital health content has fundamentally transformed how Generation Z adopts wellness habits, yet it also introduces risks such as health misinformation and unrealistic body ideals. This study is significant as it explores social media's role within Bali’s global wellness hub. Despite extensive marketing literature, a research gap exists regarding how influencers move beyond transactional promotion toward the long-term internalization of preventive health behaviors. This research aims to analyze the communication strategies and impression management techniques used by Bali based wellness influencers to cultivate sustainable lifestyles. Utilizing a qualitative descriptive method, data were gathered through the triangulation of digital observations on TikTok and Instagram, semi-structured interviews, and documentation. Findings reveal that influencers leverage Bali’s "aestheticized wellness" and cultural prestige to construct authenticity, shifting the focus from short-term purchase intentions to identity-driven community engagement. Specifically, integrating trends like "sober curious" and mental health awareness catalyzes significant lifestyle transformations among followers. Results further indicate that highly curated visual narratives are more effective than conventional health education in triggering behavioral changes among Gen Z. In conclusion, wellness influencers act as social architects defining new norms for holistic well-being. Future research should investigate the long-term sustainability of these shifts and how platform algorithms impact the dissemination of preventive health messages.